(untitled) (International Journal of Engineering and Computer Science, 2018)
In general, testing is one of the most important part of software development lifecycle (SDLC).Now a days, usage of internet is increasing rapidly, so it becomes necessity to test the websites. The web testing is more complicated as it involves different testing strategies and tools, because the tool has to support different characteristic properties and also different frameworks. So there is need to test websites as early as possible so that you will get require result in less time. The main objective of our project is to develop a time and cost effective web testing environment using selenium grid and spot instances of AWS (Amazon Web Service) on cloud to reduce testing Time using selenium grid on multiple machines and to reduce testing Cost by use of lower cost spot instances of Amazon Web Services (AWS).